Legionella pneumonia with multiple lung abscesses - A. L. Rossina; S. B. Chuelov; N. V. Kondratenko; A. A. Korsunskiy; O. A. Kaschenko; L. I. Feldfiks; I. R. Erdes; L. E. Sokolovskaya; O. V. Shamsheva (Детские инфекции (Москва))
A case of bilateral polysegmental destructive legionella pneumonia with the formation of multiple lung abscesses in an immunocompetent boy aged 15 years is presented.The child had symptoms of intoxication with febrile fever, myalgia, unproductive cough, respiratory failure, dull percussion sound and weakening of breathing on both sides in the lower sections. A computed tomography of the chest revealed multiple bilateral multifocal foci of pulmonary tissue with destruction. The diagnosis of legionella pneumonia was made on the basis of detection of IgM antibodies to L. pneumophila with an increase in titer in the dynamics and exclusion of other causes of lung damage. Levofloxacin turned out to be an effective antibacterial drug.It is necessary to take into account the ability of microorganisms of the genus Legionella to cause multiple abscess formation of lung tissue.